Design and fabrication of iron board / Faris Danial Fairuz and Radzi Abdul Rasih - Fairuz, Faris Danial; Abdul Rasih, Radzi (School of Mechanical Engineering, 2023)
Many households, particularly apartments, hostels, and flats, face a common challenge of limited storage space for items such as clothes, hangers, and ironing boards. Typically, consumers, particularly housewives, have to retrieve clothes from hangers before ironing them, which can be a time-consuming task. To address this issue, a combined clothes hanger and ironing board can be introduced, offering convenience and efficiency. By integrating the hanger alongside the ironing board, users can streamline the process and reduce their workload, making ironing clothes a more enjoyable experience. The primary objective of this project is to optimize space utilization within the house and alleviate the burden on users. Existing ironing boards often lack user-friendliness and have limited functionality. Therefore, the successful implementation of this project will eliminate the need for users to juggle clothes while ironing